Analysis of Grid-connected Solar PV System Operation based on Energy Router Concept - Ahmed Mohamed, Ahmed Haidar; Fatihah, Ramli; Andreas, Helwig (2022)
The major limitation when using renewable energy resources is their inherent variability and dependence on climatic conditions. However, routing coordination of these resources with backup power can provide a reliable and economical electricity supply under different load demand conditions. This paper proposes the concept of routing in electrical networks to compensate for the energy deficit and manage the power transfer control in grid-connected and islanded modes. The coordination management of electrical energy resources in terms of active or reactive power is adopted using a routing matrix. A fuzzy approach is applied to realize the control mechanism from the routing topology perspective. The results show that the routing scheme meets the requirements of bidirectional power flow, where the balance of active power and the compensation of reactive power can be achieved.